HIF-1α mediates hypertension and vascular remodeling in sleep apnea via hippo–YAP pathway activation - Shoude Zhang; Yuan Zhao; Zhanwei Dong; Mao Jin; Ying Lu; Mina Xu; Hong Pan; Guojin Zhou; Mang Xiao (Molecular Medicine)
Abstract Background Sleep apnea syndrome (SAS) is associated with hypertension and vascular remodeling. Hypoxia-inducible factor-1α (HIF-1α) and the Hippo–YAP pathway are implicated in these processes, but their specific roles remain unclear. This study investigated the HIF-1α/Hippo-YAP pathway in SAS-related hypertension. Methods We established a rat model of SAS-induced hypertension via chronic intermittent hypoxia (CIH). Rats were treated with siRNA targeting HIF-1α. Blood pressure, inflammation, oxidative stress, vascular remodeling, and VSMC function were assessed. In vitro experiments with A7r5 cells and human aortic smooth muscle cells (HAoSMCs) explored the effects of HIF-1α silencing and YAP1 overexpression. Results Compared with the control group, the CIH group presented significant increases in both HIF-1α and YAP1 expression, which correlated with increased blood pressure and vascular changes. HIF-1α silencing reduced hypertension, oxidative stress, inflammation, and the severity of vascular remodeling. Specifically, siRNA treatment for HIF-1α normalized blood pressure, decreased the levels of oxidative damage markers (increased SOD and decreased MDA), and reversed the changes in the levels of inflammatory markers (decreased high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6) and soluble E-selectin (sE-s)). Structural analyses revealed reduced vascular smooth muscle cell proliferation and collagen deposition, along with normalization of cellular markers, such as α-SMA and TGF-β1. Furthermore, the Hippo–YAP pathway appeared to mediate these effects, as evidenced by altered YAP1 expression and activity upon HIF-1α modulation. Conclusions Our findings demonstrate the significance of the HIF-1α/Hippo-YAP pathway in CIH-induced hypertension and vascular remodeling. HIF-1α contributes to these pathophysiological processes by promoting oxidative stress, inflammation, and aberrant VSMC behavior. Targeting this pathway could offer new therapeutic strategies for CIH-related cardiovascular complications in SAS patients.